TREN PENELITIAN PEMAHAMAN KONSEP MATEMATIS SISWA MELALUI MODEL DAN MEDIA PEMBELAJARAN INOVATIF: SLR - Anisa, Putri Mutiara; Aminah, Neneng; Shafinaz, Shafinaz (Prodi Pendidikan Matematika FKIP Universitas Madura, 2025)
Understanding mathematical concepts is an important foundation in mathematics learning, but many students still experience difficulties at this point this research aims to analyze efforts to improve students' understanding of mathematical concepts through the application of innovative learning models and media. The method used is systematic literature review (SLR) with the PRISMA approach, including identification, screening, feasibility, and inclusion of articles. From the initial 1,279 articles, 5 relevant articles were selected that met the publication criteria for 2020-2024, were in English and indexed by the DOAJ. The results of the study show that learning models such as discovery learning, problem-based learning (PBL) assisted by generative learning significantly improve students' understanding of mathematical concepts. Learning media such as geogebra have proven effective in visualizing abstract concepts, while collaborative and problem-based approaches encourage active student engagement. These findings confirm the importance of selecting appropriate learning models and media to create an interactive and in-depth learning environment, the implication of this research is the need for teachers to integrate evidence-based learning innovations to improve the quality of mathematics education in Indonesia.